After Nikolai Bukharin: History of science and cultural hegemony at the threshold of the Cold War era. (October 2016) - Omodeo, Pietro D.
This article addresses the ideological context of twentieth-century history of science as it emerged and was discussed at the threshold of the Cold War. It is claimed that the bifurcation of the discipline into a socio-economic strand and a technical-intellectual one (the divide between 'externalism' and 'internalism') should be traced back to the 1930s. In fact, the proposal of a Marxist-oriented historiography by the Soviet delegates at the International Congress of History of Science and Technology (London, 1931) led by Nikolai Bukharin, set off the ideological and methodological opposition that characterised the later years. Bukharin's views on science are closely considered, as well as those of his Marxist critics, György Lukács and Antonio Gramsci. It is argued that, despite the fluidity of the positions of the 1920s and 1930s, these theories soon crystallized as demonstrated by the leftist reception of Bukharin's and his associates' perspective in the history of science, especially in Great Britain, as well as by the anti-communist reactions. Intellectualist approaches renouncing socio-economic factors, typically those by Alexandre Koyré and Thomas Kuhn, are reconsidered in the light of the ideological confrontation of the Cold War era. Reflection on the political-cultural embedding of the history of science has often been overshadowed by claims about the objectivity and neutrality of science and its historiography. Thus, the seminal discussion of the 1930s remains one of the most lucid moments of reflection about the role of science and history of science as cultural phenomena shaped by political struggles.